Impact of use of illustration in the presentation of Neuroanatomy through the analyses of the illustration in the Neuroanatomy text books commonly used by the medical postgraduates of Bangladesh - Yasmin, Quazi Shamsunnahar; Banu, Laila Anjuman; Rahamn, Md. Fashiur; Hossain, Samira; Akhter, Zakia (Bangladesh Journal of Anatomy, 2013)
Bangladesh Journal of Anatomy, January 2012, Vol. 10 No. 1 pp 27-31 DOI: http://dx.doi.org/10.3329/bja.v10i1.15756